2007
DOI: 10.3758/bf03193486
|View full text |Cite
|
Sign up to set email alerts
|

Paying attention to binding: Further studies assessing the role of reduced attentional resources in the associative deficit of older adults

Abstract: The present experiments investigated whether the observed associative deficit in older adults' episodic memory is mediated by a reduction of attentional resources. Using a dual-task procedure, younger and older participants studied lists of word pairs either under full attention or while performing a concurrent task. Both experiments showed that dividing attention did not cause a greater impairment to memory for associations than to memory for items in either age group. Furthermore, an analysis of concurrent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
67
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 44 publications
10
67
1
Order By: Relevance
“…One influential account, that is consistent with predictions from McDaniel and Einstein's multiprocess model, proposes that this deficit is a consequence of age-related decrements in attentional resources (e.g., Craik, 1983;Rabinowitz, Craik & Ackerman, 1982). Numerous studies have provided support for this proposal using the contrast between performance under divided and full attention in younger adults (e.g., Kilb & Naveh-Benjamin, 2007; Naveh-Benjamin, Guez, Kiln & Reedy, 2004). Other studies, however, have failed to observe an age-related effect of attentional demands on associative compared with item information recognition memory (e.g., NavehBenjamin, Guez & Marom, 2003).…”
Section: Introductionsupporting
confidence: 51%
“…One influential account, that is consistent with predictions from McDaniel and Einstein's multiprocess model, proposes that this deficit is a consequence of age-related decrements in attentional resources (e.g., Craik, 1983;Rabinowitz, Craik & Ackerman, 1982). Numerous studies have provided support for this proposal using the contrast between performance under divided and full attention in younger adults (e.g., Kilb & Naveh-Benjamin, 2007; Naveh-Benjamin, Guez, Kiln & Reedy, 2004). Other studies, however, have failed to observe an age-related effect of attentional demands on associative compared with item information recognition memory (e.g., NavehBenjamin, Guez & Marom, 2003).…”
Section: Introductionsupporting
confidence: 51%
“…Although several studies in the literature actually showed that younger adults under DA conditions exhibited patterns of memory performance decline similar to those of older adults (e.g., Craik & Byrd, 1982;Rabinowitz, Craik, & Ackerman, 1982), when younger adults study items and associations under DA, their memory performance for items and associations suffers to the same degree relative to those tested under full attention conditions, unlike the differential patterns of performance in older adults. Such a pattern is not in line with the reduction in attentional resources hypothesis, but instead supports an independent associative mechanism as the source of older adults' episodic memory decline (Naveh-Benjamin, Guez, & Shulman, 2004;Naveh-Benjamin et al, 2003;Kilb & Naveh-Benjamin, 2007). The present study is intended to further test the ADH and contrast it with another major hypothesis regarding older adults' deficits in episodic memory, one that attributes these deficits to a failure of inhibitory processes (e.g., Hasher & Zacks, 1988).…”
mentioning
confidence: 50%
“…However, similar to the results reported in Experiments 1 and 2, this effect of reduced inhibitory control in the memory task affected both item and associative memory to the same degree, rather than showing a differential effect as in older adults. The inhibitory concurrent task served as a DA manipulation exactly as the comparable facilitation concurrent task and as reported in other studies regarding DA effects on item and associative recognition, such a manipulation results in additive effects on item and associative memory tests (Naveh-Benjamin et al, 2003;Naveh-Benjamin, Guez, & Shulman, 2004;Kilb & Naveh-Benjamin, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…However, in the current study associative memory and the recollection-based item-memory task (free recall) were also unrelated, suggesting that poorer associative memory did not solely originate from a decrement in recollection. Hence, to bind two elements together may not only be more difficult than remembering a single item (see also Kilb and Naveh-Benjamin, 2007), but also to depend on processes that go beyond recollection. Such processes might be unique for the cognitive operation of binding two or more pieces of information and occur at different levels, including low-level perceptual binding, binding of items, and integration of events with their context.…”
Section: Inter-individual Differences In Associative Memory Are Indepmentioning
confidence: 98%